Tight-binding analysis of topological materials and new directions in optical tweezers - Campos, Warlley Hudson (2021)
Optical tweezers (OT) is a powerful technique to manipulate microscopic objects using light. Dielectric particles are stably trapped, while metallic beads are usually deflected by radiometric forces. The optical trapping of semi-transparent particles have been over- looked in the literature. In this regard, we have observed that Bi 2 Te 3 , Bi 2 Se 3 [both are topological insulators (TI’s)] and germanium particles behave like optically induced oscillators under a Gaussian laser beam OT. The oscillations take place in a plane per- pendicular to the optical axis of the laser beam as a result of the competition between gradient and radiometric forces. Remarkably, the oscillation direction of the germanium particles depends on the polarization of the laser beam. We propose an effective model to describe these effects, which reproduces the experimental data with good accuracy. Furthermore, we propose a generalization of the Ashkin’s model for OT in the geometri- cal optics regime, accounting for light absorption by the trapped particle. We have also studied the interplay between topological materials and magnetic ordering. These materi- als exhibit very unusual properties, such as metallic surface states with “spin-momentum locking” in TI’s and corner-localized states in second order TI’s. Here, we show that an electrically charged wire near a semi-cylindrical cavity in a TI can be used to induce a Hall current reversion on its surface. Furthermore, preliminary investigations have indicated higher order topology on spinful ferromagnetic and antiferromagnetic variations of the 2D SSH model. Similar analysis have shown that an effect analogous to the topological metal-insulator transition for antiferromagnetic CuMnAs takes place in its ferromagnetic variation. Among the possible applications of our results, stand out the optical rheol- ogy of soft matter interfaces, dynamical force measurements in macromolecules, colloid science and biopolymers, as well as a possible experimental realization of a microscopic single-particle thermal machine. In turn, topological materials are quoted as promising candidates for near future technology, with possibilities for applications in spintronics, quantum computation and advanced low-dissipation devices. Keywords: Topological Materials. Optical Tweezers. Semiconductors. Topological Insulators.